Characterization of Neutrophil Function in Human Cutaneous Leishmaniasis Caused by Leishmania braziliensis. - Jacilara Conceição; Richard Davis; Pedro Paulo Carneiro; Angela Giudice; Aline C Muniz; Mary E Wilson; Edgar M Carvalho; Olívia Bacellar (Public Library of Science (PLoS), 2016)
Infection with different Leishmania spp. protozoa can lead to a variety of clinical syndromes associated in many cases with inflammatory responses in the skin. Although macrophages harbor the majority of parasites throughout chronic infection, neutrophils are the first inflammatory cells to migrate to the site of infection. Whether neutrophils promote parasite clearance or exacerbate disease in murine models varies depending on the susceptible or resistant status of the host. Based on the hypothesis that neutrophils contribute to a systemic inflammatory state in humans with symptomatic L. braziliensis infection, we evaluated the phenotype of neutrophils from patients with cutaneous leishmaniasis (CL) during the course of L. braziliensis infection. After in vitro infection with L. braziliensis, CL patient neutrophils produced more reactive oxygen species (ROS) and higher levels of CXCL8 and CXCL9, chemokines associated with recruitment of neutrophils and Th1-type cells, than neutrophils from control healthy subjects (HS). Despite this, CL patient and HS neutrophils were equally capable of phagocytosis of L. braziliensis. There was no difference between the degree of activation of neutrophils from CL versus healthy subjects, assessed by CD66b and CD62L expression using flow cytometry. Of interest, these studies revealed that both parasite-infected and bystander neutrophils became activated during incubation with L. braziliensis. The enhanced ROS and chemokine production in neutrophils from CL patients reverted to baseline after treatment of disease. These data suggest that the circulating neutrophils during CL are not necessarily more microbicidal, but they have a more pro-inflammatory profile after parasite restimulation than neutrophils from healthy subjects.